PHYSICAL ACTIVITY AND IMMUNE FUNCTION: IMPLICATIONS FOR RESPIRATORY INFECTIONS AND VACCINE IMMUNOGENICITY – A NARRATIVE REVIEW - Viktoria Kretschmer; Magdalena Baranowska; Zuzanna Dynowska; Dominik Poszwa; Daniel Markowski; Patryk Kondracki; Wiktor Daniszewski; Ewa Sobolewska; Jakub Rodziewicz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Physical activity is widely recognized as an important modifier of immune function. Numerous studies have examined exercise-induced changes in cellular and mucosal immunity and their implications for susceptibility to acute respiratory infections and vaccination outcomes. However, the clinical relevance of post-exercise immune alterations remains debated.Aim: The review aimed to synthesize current evidence regarding the influence of acute and chronic physical activity on immune regulation, respiratory infection risk and vaccine immunogenicity in adults.Material and Methods: A narrative literature review was conducted using PubMed, PubMed Central and Google Scholar. English-language studies involving adults were included, with priority given to articles published from 2010 onward. Particular attention was paid to relationships between physical activity, immune function, upper respiratory tract infections and vaccine responses.  Results: Regular moderate physical activity is associated with improved immune surveillance and higher resting mucosal immunity markers. Although strenuous exercise induces transient immune alterations, evidence for a clinically meaningful increase in infection risk remains inconsistent. Epidemiological data suggest that physically active individuals generally experience fewer symptomatic days and reduced illness severity. Long-term exercise participation is linked to modestly improved post-vaccination antibody responses, especially in older adults. Single exercise sessions performed around immunization show often minimal effects.Conclusions: Habitual moderate physical activity supports more efficient immune regulation and may reduce respiratory disease burden. Short-term post-exercise immune fluctuations appear largely adaptive rather than clinically immunosupressive. Physical activity may serve as an accessible adjunct strategy to enhance vaccination outcomes, however, further high-quality trials using objective clinical endpoints are required.